Starania o ustawę. Studium jednego przypadku: [Endeavours after an act — a study of one case] (Studia Prawnicze / The Legal Studies, 2023)
Referring to the Act of September 27, 1973 on the old age pensions for artists and their families, the author of this paper has analysed the endeavours after political decisions, that took several years, and were indispensable to carry out the respective legislation. According to the Constitution an obligation arises to enact a law and extend the rights to those groups which were deprived of them (under the Article 60 and 65 of the Constitution — according to the previous numbering). Moreover, the standpoint of the Sejm, as expressed in its resolution, precludes a possibly different government assessment as to the necessity to enact law (in a form of an act). It has also been stated that when opposing the attempts of the administration to be commissioned to issue a decree that would regulat'd the whole problem, both the deputies and artists considered the latter to be within the scope of legislation and therefore the Sejm should ensure that appropriate measures be taken. The author has concluded by saying that the ”problem” of the act was neither of financial or social nature, nor the outcome of the state pensions policy, nor the manifestation of the state’s attitude towards culture. On the one hand the problem arose because the act was treated as an expedient of the policy towards artists, and on the other, because the latter referred to civil rights in this respect. According to the author there was the interdependence between the pace of endeavours after the act and the political climate at the time. He has also pointed to the interdependence between the standpoint of the party and the legal guarantees that the constitution is enforced and the Sejm holds a superior position. The author has stressed how important that' incident was both for democratizing the legislative function (i. e. the extension of the circle of legal subjects, the commitment of the public opinion, availing of those legal measures that are rich in democratic contents) and enriching the attitudes (in terms of subject-matter) towards the act on old age pensions, particularly the significant role the Sejm and artists played.